Electronic Catalog-Based Procurement of Clinical Laboratory Goods and Services: An Evaluation Study at Tabanan Regional General Hospital - I Wayan Eddy Arimbawa; Putu Ayu Parwati; Anak Agung Ayu Eka Cahyani (Jurnal Laboratorium Khatulistiwa, 2026)
Procurement of clinical laboratory goods and services is a critical component in ensuring the continuity, quality, and efficiency of healthcare services. In Indonesia, electronic catalogs (e-catalogs) have been implemented as part of the government’s digital procurement system to enhance transparency, accountability, and efficiency in public procurement. However, several studies have reported operational challenges that may affect procurement effectiveness, including limited product availability, system constraints, and procurement delays. This study aimed to evaluate the implementation of electronic catalog-based procurement for clinical laboratory goods and services at Tabanan Regional General Hospital. A quantitative observational study was conducted using procurement reports from January 2024 to June 2025. All procurement transactions conducted through the electronic catalog system were included using a total sampling approach. Data were analyzed descriptively to determine the percentage of successful procurement implementation and identify factors influencing procurement performance. The results showed that the average implementation rate of electronic catalog-based procurement reached 84.1%. Several factors contributed to procurement constraints, including frozen or unavailable products in the electronic catalog, minimum order quantity requirements, and automatic package cancellation due to negotiation time limits. Despite these challenges, the electronic catalog system provided significant advantages by offering standardized information on product specifications, pricing, domestic content requirements, supplier profiles, environmental certification, and other procurement-related data. The study concludes that electronic catalog-based procurement is generally effective in supporting clinical laboratory procurement activities; however, system optimization and improved supplier participation are required to maximize procurement performance and service continuity.